Inclusive education in resource-constrained settings: exploring mainstream teachers’ curriculum knowledge and practices for autistic learners in South Africa - Sepadi, Medwin (Frontiers in Education, 2025)
This study investigated mainstream educators’ understanding of Autism Spectrum Disorder (ASD) in South Africa’s Tzaneen Circuit, aiming to assess their knowledge, attitudes, and classroom practices regarding inclusive education for autistic learners. Despite progressive policies like White Paper 6 (2001), implementation gaps persist in rural areas due to limited training and resources. Using a qualitative case study design, data from six educators revealed limited ASD knowledge primarily gained through informal means, positive but strained attitudes toward inclusion, and systemic challenges like overcrowded classrooms and lack of specialist support. While educators demonstrated adaptive strategies, the findings highlight critical needs: enhanced teacher training, accessible resources, and stronger policy implementation to achieve equitable inclusion. The study underscores the urgency of addressing these gaps in under-resourced settings through collaborative, systemic reforms to empower educators and improve outcomes for autistic students.